Tuberculous pseudotumor of fibular head - Thapa, Sunil Singh; Lamichanne, Arjun; Mahara, Deepak Prakash (Journal of Society of Surgeons of Nepal, 2017)
Tuberculous osteomyelitis of long tubular bone is uncommon, the reported incidence is about 2-3 %. Tuberculous osteomyelitis of fibular head is very rare and it mimics neoplasm. Here we report a case of a 28 year old male presenting with unremitting right knee pain with swelling around fibular head with knee radiography showing lytic lesion of proximal fibula,excisional biopsy was done and histopathological report confirmed it as tuberculous osteomyelitis. Journal of Society of Surgeons of Nepal, 2015; 18 (2), page: 33-35